The Role of Green Self-Identity and Perceived Consumer Effectiveness in Shaping Green Purchase Intention Among Generation Z - Dharmawati, Desy; Harwani, Yuli; Nurmahdi, Adi; Wulandari, Ririn (International Journal of Economics, Business, and Entrepreneurship, 2025)
This study investigates the influence of green self-identity and perceived consumer effectiveness on green purchase intention among Generation Z consumers in Indonesia. Using a quantitative, causal-explanatory approach, data were collected through an online survey involving 350 respondents residing in the Jabodetabek area. Structural Equation Modeling–Partial Least Squares (SEM-PLS 4.0) was employed to test the hypothesized relationships. The results indicate that both green self-identity and perceived consumer effectiveness have a significant and positive effect on green purchase intention. Green self-identity emerges as the dominant predictor, suggesting that internalized environmental self-concept strongly motivates sustainable purchasing behavior. These findings align with the Theory of Planned Behavior, which emphasizes the role of self-concept and perceived control in behavioral intention. Practically, the study provides actionable insights for marketers and policymakers to strengthen sustainable branding strategies targeting young consumers. Enhancing consumers’ sense of personal responsibility and environmental identity can foster long-term pro-environmental commitment. Theoretically, the study contributes to the development of sustainability marketing by validating identity-based and efficacy-based constructs within an emerging market context.